ARANSEMEN LAGU ELE MOTO MEDLEY DENGAN DO DAE MATA B’ALE DALAM FORMAT COMBO BAND ADDITIONAL ALAT MUSIK TRADISIONAL - Ruth Regina Djuka (Tambur : Journal of Music Creation, Study and Performance, 2022)
The research objective of arranging the songs of Ele Moto and Do Dae Mata Bale is to compose and describe the arrangement of the songs of ele moto medley with the song do dae mata bale in a combo band format so that the song can be an inspiration for the younger generation to continue to develop regional traditions through traditional music that there is. The research method used in this research is to use descriptive qualitative analysis techniques, namely searching, analyzing, describing data and compiling data systematically form interviews, field notes and documentation, by organizing data into categories such as: data reduction, data presentation, verification or data deduction to obtain correct data. The results of this study indicate the presentation of the music arranged in a combo band format, the song Ele Moto and Do Dae Mata B’ale into a pop music genre presentation. Instruments used in the combo band format arrangement are : Piano, flute, trumpet, trombone, bass, gong and drum.